Single-input and three-output current-mode universalfilter using a reduced number of active elements - Ozoguz, S.; Acar, C. (Institution of Engineering and Technology (IET), 1998)
A new single-input and three-output current-mode universal filter, using only four operational mirrored amplifiers, is presented. It is shown that the filter is better than existing current conveyor-based universal current filters. Experimental results verifying the theoretical analysis are also included.